Jack: Straight from the Gut - Byrne , john A.; Aneet, (Gyan Management Journal, 2008)
Jack Welch was born on November 19, 1935 in Peabody, Massachusetts. He had a humble upbringing, his father worked as a conductor on the rail line connecting Boston and Newburyport.Jack spent his early childhood years in Salem, Massachusetts. His father was a regular visitor at GE's Aircraft Engine' Complex in Lynn just out.side Boston, but who would have imagined that this was the company thatJack would go on to head one day. The greatest gift that Jack's mother gave him was selfconfidence. His father would come home with a bundle of newspapers under his arm, all of them left by his passengers on the train.Jack was also encouraged by his father to learn golf as all the big shots on his train were always talking about their golf games. At the age of nine, Jack started caddying at the nearby Kenwood Country Club. Besides caddying, Jack juggled between many jobs-like delivering the Salem Evening ews and working for the local post office during holidays.
Keywords: Massachusetts; Newburyport; selfconfidence; Jack